Effect of thermal oxidation temperature on rutile structure formation of biomedical TIZRNB alloy - Izman, Sudin (2012)
Wear debris and metal ion release generated during application of biomedical devices would cause adverse cellular response, inflammation and pain in the human body. Modifying of implant surface with rutile structure is one of the methods to reduce these problems. In the present study, an attempt was made to evaluate the effect of thermal oxidation temperature on surface morphology and structure of the Ti13Nb13Zr biomedical material. The substrates were heated at varied temperatures of 550°C, 700°C and 850°C for 9 hours and cooled inside muffle furnace at a constant rate of 5oC/min. Scanning electron microscopy and x-ray diffractive were employed to evaluate the surface morphology and analyze the structure of the oxidized substrates respectively. All thermally oxidized samples exhibit the presence of oxides without spallation regardless of the thermal oxidation temperatures. Surface morphology of oxidized substrates changes from smooth to nodular particles-like shape when the oxidation temperature increases from low to high. Rutile structure dominants the surface area when the substrate is thermally oxidized at 850 °C.